Targeted inhibitors of S100A9 alleviate chronic pancreatitis by inhibiting M2 macrophage polarization via the TAOK3-JNK signaling pathway - Tao, Xufeng; Wu, Yu; Guo, Fangyue; Lv, Linlin; Zhai, Xiaohan; Shang, Dong; Yu, Zhan; Xiang, Hong; Dong, Deshi (Frontiers in Immunology, 2025)
BackgroundChronic pancreatitis (CP) is a fibro-inflammatory syndrome with unclear pathogenesis and futile therapy. CP’s microenvironment disrupts the fine-tuned balance of macrophage polarization toward a predominance of the M2-like phenotype associated with fibrosis. S100A9 is mainly expressed in monocytes as a potent regulator of macrophage phenotype and function. Here, we investigated the S100A9-related mechanisms underlying CP pathology induced by macrophages polarization.MethodsS100a9 knockout (S100a9-/-) mice and an in vitro coculture system of macrophages overexpressing S100a9 and primary PSCs were constructed to investigate the effects and mechanisms of S100A9-mediated macrophage polarization on pancreatic inflammation and fibrosis underpinning CP pathology. Furthermore, a variety of S100A9-targeted small-molecule compounds were screened from U.S. Food and Drug Administration (FDA)-listed drug libraries through molecular docking and virtual screening techniques.ResultsIn CP progression, S100A9 upregulation induces M2 macrophage polarization to accelerate fibrosis via thousand-and-one amino acid kinase 3 (TAOK3)-c-Jun N-terminal kinase (JNK) signaling pathway, and loss of S100A9 reduces CP injury in vitro and in vivo. Coimmunoprecipitation (co-IP) and molecular docking experiments proved that S100A9 may interact directly with TAOK3 through salt bridges and hydrogen bonding interactions of the residues in the S100A9 protein. Furthermore, cobamamide and daptomycin, as inactivators of the S100A9-TAOK3 interaction, can improve CP by inhibiting the polarization of M2 macrophages.ConclusionsS100A9 is a significant promoter of M2-like macrophage-induced fibrosis in CP via the TAOK3-JNK signaling pathway. Cobamamide and daptomycin, targeted inhibitors of the S100A9-TAOK3 interaction, may become candidate drugs for CP immunotherapy.